Recycling of Waste Plastic to Produce Alternative Synthetic Fuel Via Pyrolysis Process - Amhemmad Aboueqeelah Masoud; Mohamed Baqar (African Journal of Advanced Pure and Applied Sciences, 2024)
Waste plastic is considered the third after natural gas and crude oil in terms of energy consumption in power plants. Despite the increase in waste plastic around the world, the major challenge for sustainable development is the elimination of environmental pollutants through ecologically friendly alternatives. Unlike incineration, pyrolysis produces no poisonous or environmentally detrimental emissions. In this study, a pyrolysis technique via catalyst was used to transform waste plastic into oil in an effort towards an environmentally beneficial way. The pyrolysis has been conducted in the absence of oxygen and at a temperature of about 350 °C. The system understudy consists of plastic garbage collected from a variety of sources including households, hotels, and markets. The garbage is sorted according to classification family into categories to represent the following polymers; polyethylene terephthalate (PET), high density polyethylene (HDPE), low-density polyethylene (LDPE) and polypropylene (PP). The study showed the successes of using the pyrolysis method to recover fuel oil from the systems understudy. Among the systems, waste PP exhibited a yield value of about 89% followed by LDPE and HDPE with 65% and 53% at 420 °C, respectively. Generally, the produced fuel oil has shown comparable results similar to that of common petroleum products.